Theoretical Analysis on the Possible Interruption of Cell Division by Applying Physical Excitation to Gold Nanoparticles Introduced in Chromosomes - Naruse, Yujiro (Journal of Membrane and Separation Technology, 2013)
Theoretical analysis on cell division control using physical excitations for biocompatible gold nanoparticles in chromosomes is performed. The methods of physical excitations are utilizing ultrasound, electromagnetic waves and X-rays. Due to the mass increase of chromosomes, ultrasound enhances the vibration of chromosomes in metaphase of mitosis, which will disturb the alignment of chromosomes on metaphase plates and will suppress cell divisions. Under the exposure of electromagnetic waves, gold wires composed of gold nanoparticles will act as antennas in chromosomes, which will absorb electromagnetic energy and increase the temperature of chromosomes. There is a possibility that the temperature rise will bring about the transformation of DNA structure and interrupt the mitosis process. Gold nanoparticles exposed by X-rays in chromosomes emit high energy electrons through photoelectric effect, which will bring about a possibility that the high energy electrons will break the DNA structure and suppress mitosis process.